The militarization of childhood : thinking beyond the global south - Beier, J. Marshall (New York, NY : Palgrave Macmillan, 2011)
"In its various manifestations, the campaign to end child soldiering has brought graphic images of militarized children to popular consciousness. In the main, this has been a campaign that has seemed to speak to African contexts without as much reflection on the myriad ways in which the lives of children are militarized in advanced (post)industrial societies. Proceeding from this quite striking omission, the contributors to this volume move beyond the usual focus on the global South. Making what will be an important contribution to a much needed critical turn in the vast and still rapidly growing child soldier literature, they address multifarious ways in which childhood is militarized beyond the global South through enactments of militarism that have drawn much less in the way of critical inquiry"--
"Thinking beyond the global South and recognizing that militarism circulates and interpenetrates childhood experience in ways that are much less conspicuous than child soldiering raises questions of critical relevance to but not yet taken up in the disciplinary study of international relations. The contributors to this volume inquire into the relationship between militarism and childhood in advanced (post)industrial societies and ask what can be learned about its sources and implications. Together they provide an important corrective to too narrow a focus on zones of conflict that might make it seem as though militarism operates through the lives of children only in distant and politically fraught places"--
Machine generated contents note: -- (Neo) Zones of Violence: Reconstructing Children into Militants and Insurgents and Empire--Anna M. Agathangelou and Kyle D. Killian * 'Guardians of the Peace'?: The Significance of Children to Continued Militarism--Alison M.S. Watson * Militarized Children and Bare Childhood--Lorraine Macmillan * Education and the War on Terror: The Early Years--Helen Brocklehurst * War Stories: Militarized Pedagogies of Everyday Parenting--J. Marshall Beier * Superheroes or Supersoldiers? Are Caped Crusaders the New Face of the Military?--Lori A. Crowe * Outsmarting the Weapons: The World of 'Us' Against 'Them'--Claire Turenne Sjolander * Where the Wild Things Are: Imaginative Disembodiment and the Militarization of Childhood--Lesley Copeland * Sometimes It's Good to be Bad: Young People and Symbolic Experimentation with the 'Darkside' in On- and Off-line Role Playing Games--Nic Crowe * Kids with Guns: Militarization, Masculinities, Moral Panic and (Dis)Organised Violence--Victoria M. Basham * Childhood Militarization and Race Relations: The Case of Omar Khadr and the Canadian State--Jessica E. Foran * Peace Through Superior Firepower: Reflections on a Militarized Childhood--Heather A. Smith, Maureen Smith, and Ross Smith.
Includes bibliographical references (p. [255]-286) and index.
Keywords: Children and war -- Developing countries; Child soldiers -- Developing countries; SOCIAL SCIENCE / Children's Studies; SOCIAL SCIENCE / Regional Studies; POLITICAL SCIENCE / Colonialism & Post-Colonialism.